2019
DOI: 10.1002/pssr.201800565
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Dimensional GaX/SnS2 (X = S, Se) van der Waals Heterostructures for Photovoltaic Application: Heteroatom Doping Strategy to Boost Power Conversion Efficiency

Abstract: Two‐dimensional (2D) heterostructures with novel and tunable physical properties are regarded as promising candidates for high‐efficiency photovoltaics. The band gap and band alignment at the interface are fundamental properties determining photovoltaic‐device efficiency. Here, by systematic first‐principles density‐functional calculations, we demonstrate that 2D GaX/SnS2 (X = S, Se) van der Waals heterostructures with a narrow band gap are solar cell candidate materials. The results show that compared to thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 50 publications
(67 reference statements)
1
16
0
Order By: Relevance
“…The wide bandgap offers more opportunity for tuning the band alignment between the heterojunctions. For example, Wu et al investigated the bandgap and band alignment in 2D GaX/SnS 2 (X = S, Se) vdW heterostructures based on density functional theory calculations. They predicted that the obtained heterostructures possess a large built-in potential which would facilitate the separation and migration of photoexcited electron–hole pairs, hence reducing the recombination rate.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The wide bandgap offers more opportunity for tuning the band alignment between the heterojunctions. For example, Wu et al investigated the bandgap and band alignment in 2D GaX/SnS 2 (X = S, Se) vdW heterostructures based on density functional theory calculations. They predicted that the obtained heterostructures possess a large built-in potential which would facilitate the separation and migration of photoexcited electron–hole pairs, hence reducing the recombination rate.…”
Section: Applicationsmentioning
confidence: 99%
“…(b) Light absorption spectra of each monolayer (GaX and SnS 2 ) and GaX/SnS 2 heterostructures. Reproduced with permission from ref . Copyright 2019 Wiley-VCH.…”
Section: Applicationsmentioning
confidence: 99%
“…Forming a semiconductor interface enables the creation of the advanced characteristics and properties that are currently lacking in a single 2D material. Heterostructures formed by stacking 2D semiconducting materials via weak van der Waals (vdW) forces have been widely investigated theoretically and experimentally. These vertical stacked heterostructures not only preserve the intrinsic electronic prosperities of the single materials but also enhance the electronic and optical properties. , Moreover, various heterostructures have been successfully synthesized to date. For instance, Gong et al reported their effective fabrication of WSe 2 /MoSe 2 heterostructures by a two-step method using chemical vapor deposition (CVD). Tongay et al fabricated WS 2 /MoS 2 heterostructures by employing the CVD method.…”
Section: Introductionmentioning
confidence: 99%
“…根据定义, 太阳能电池材料的性能可以通过能量转换效率(power conversion efficiency, PCE)来定量 评估 [50] : [51] , E g 和 ΔE c 分别是施主带隙和导带偏移(conduction band offset, CBO 异质结构太阳能电池,如 PCBM/CBN(10-20%) [52] ,g-SiC/GaN(12-20%) [53] ,SnO 2 /TiO 梯度异质结 (18.08%) [54] , 2D GaX/SnS 2 (16%) [55] , 钙钛矿基异质结构(21.02%) [56] 和 BP/SnSe(17.24%) [57] recombination of carriers. Therefore, the electrons and holes that can be actually used in the reaction are significantly reduced.…”
Section: 实际反应中,催化剂的能带边缘位置是决定水解反应是否可行的重要参数 理想情况下,可自发mentioning
confidence: 99%